Malaria infection of endemic primates in the Buton Utara Wildlife Sanctuary, Indonesia: Potential for transmission to humans - Meyby Eka Putri Lempang; Dendi Hadi Permana; Puji Budi Setia Asih; Suradi Wangsamuda; Farahana Kresno Dewayanti; Ismail Ekoprayitno Rozi; Wuryantari Setiadi; Lepa Syahrani; Lucia Muslimin; Ratmawati Malaka; Din Syafruddin (International Journal of One Health)
Background and Aim: Zoonotic malaria is an emerging public health challenge in Indonesia, exacerbated by deforestation and increased interaction between humans and non-human primates (NHPs). This study aimed to estimate malaria prevalence in NHPs within the Buton Utara Wildlife Sanctuary (BUWS) and evaluates the potential risk of zoonotic malaria transmission to nearby human populations.